2019
DOI: 10.1002/acn3.50890
|View full text |Cite
|
Sign up to set email alerts
|

Serum neurofilament heavy chains as early marker of motor neuron degeneration

Abstract: ObjectiveTo determine whether serum phosphorylated neurofilament heavy chain (pNfH) levels are elevated before patients were diagnosed with sporadic or familial ALS, and what the prognostic value of these prediagnostic pNfH levels is.MethodspNfH was measured via ELISA in leftovers of serum drawn for routine purposes before the time of diagnosis. These prediagnostic samples were retrieved from the biobank of the University Hospitals Leuven for 95 patients who in follow‐up received a diagnosis of ALS. Additional… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
32
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 38 publications
(33 citation statements)
references
References 20 publications
1
32
0
Order By: Relevance
“…However, the application of NF quantification at the general practitioner or first aid room may confuse rather than expedite the diagnosis of MND. On the other hand, a recent study proved that serum pNfH was already elevated above normative values in individuals admitted with early motor symptoms who only later satisfied the diagnosis of sporadic or familial ALS [108] . The lack of specificity of NFs towards neurodegenerative conditions should not alarm against their diagnostic value as far as their use is limited to experienced neurologists who can orient the diagnosis in the right direction.…”
Section: Limitations and Future Directionsmentioning
confidence: 95%
“…However, the application of NF quantification at the general practitioner or first aid room may confuse rather than expedite the diagnosis of MND. On the other hand, a recent study proved that serum pNfH was already elevated above normative values in individuals admitted with early motor symptoms who only later satisfied the diagnosis of sporadic or familial ALS [108] . The lack of specificity of NFs towards neurodegenerative conditions should not alarm against their diagnostic value as far as their use is limited to experienced neurologists who can orient the diagnosis in the right direction.…”
Section: Limitations and Future Directionsmentioning
confidence: 95%
“…In various neurological diseases, blood-based biomarkers that reflect disease progression have recently been gaining attention, including serum neurofilament light chain (sNfL). 10–25 Neurofilaments are released into blood and cerebrospinal fluid of patients with neurodegenerative diseases in whom they have been shown to be associated with various clinical features. 10–25 For example, recent studies showed significant cross-sectional associations between sNfL and disability or therapy response in various peripheral neuropathies, including in CIDP.…”
Section: Introductionmentioning
confidence: 99%
“… 10–25 Neurofilaments are released into blood and cerebrospinal fluid of patients with neurodegenerative diseases in whom they have been shown to be associated with various clinical features. 10–25 For example, recent studies showed significant cross-sectional associations between sNfL and disability or therapy response in various peripheral neuropathies, including in CIDP. 19–23 However, these studies did not yet investigate the prognostic value of sNfL in CIDP with respect to disease progression or therapy response.…”
Section: Introductionmentioning
confidence: 99%
“…The identification of mutations in the C9orf72 gene by two independent groups was a groundbreaking discovery (Renton et al, 2011; Dejesus‐hernandez et al, 2011). This mutation is responsible for ~11% of all ALS cases and ~13% of all FTD cases (Abramzon et al, 2020).…”
Section: The Progressive Nature Of Neurodegenerative Diseasesmentioning
confidence: 99%